1H Nuclear Magnetic Resonance (NMR) and Differential Scanning Calorimetry (DSC) Studies of Water Mobility in Dough Systems Containing Barley Flour. Issue 2 (1st March 2013) - Lu, Zhanhui; Seetharaman, Koushik
ABSTRACT: This study used 1 H nuclear magnetic resonance (NMR) spin‐spin relaxation time ( T 2 ) and differential scanning calorimetric (DSC) measurements of unfreezable water content (UFW), to assess water behavior in freshly prepared (25°C), refrigerator‐stored (4°C, one day), or freezer‐stored (–35°C, one day) doughs containing 5, 10, or 30% whole grain, air‐classified β‐glucan‐diminished, and air‐classified β‐glucan‐enriched (BGB‐E) barley flours. Three populations of water were detected by NMR, depending on moisture content of dough, namely, tightly ( T 21, 2–5 msec), less tightly ( T 22, 20–50 msec), and weakly ( T 23, 100–200 msec) bound water. T 22 peak was always detectable, and T 22 peak time linearly correlated to moisture content of dough in a range of 0.7–2.0 g/g db ( r = 0.99, P < 0.05). Freezer storage showed less effect on water mobility in dough compared with refrigerator storage, whereas cooking and cool storage of cooked dough significantly decreased the water mobility ( P < 0.05). Adding barley flour steadily decreased the water mobility in dough, and the reduction was more significant with adding BGB‐E ( P < 0.05). Immobile water content was calculated by extrapolating T 22 peak time versus total moisture content in dough and significantly correlated to the UFW content measured by DSC ( r = 0.72, P < 0.05).